Elastography of the Pancreas, Current View - Christoph F. Dietrich; Michael Hocke (Korean Society of Gastrointestinal Endoscopy, 2019)
Ultrasound elastography (USE) of the pancreas allows pancreatic tissue stiffness assessment by virtual palpation. Two main types of USE are used. For the pancreas strain elastography applying by endoscopic ultrasound has been established for the characterisation of small solid pancreatic lesions (SPL). In larger SPL >30 mm the results are less convincing mainly due to the heterogenicity of the lesions but also by concomitant changes of the surrounding pancreatic parenchyma. The current role of shear wave elastography has to be determined. This article reviews the current use of elastography of the pancreas.